Understanding the Mad’u: Towards an Impactful Da’wah - Khan, Musaddiq Majid (Faculty of Leadership and Management, Universiti Sains Islam Malaysia, 2017)
People who are involved in Da’wah, in contemporary times, are mostly those who lack the true understanding of the message that Islam as a religion, brings. Such lack of understanding often leads to negative effects such as hatred towards the religion. It is very important for the Dā’ī who is performing Da’wah to fully understand his audience before attempting to spread the message of Islam. He thus must have the ability to fascinate the hearts of the audience to attract them towards the message and be sensitive to the differences of human nature, intellect, and cultural background. Using analytical and descriptive methods, this paper discusses the importance of fulfilling the necessities in Da’wah, as well as the significance of true understanding of religion with regards to the called, or the mad’ū. In addition, it also explains the following seven fundamental characteristics: (1) proficiency in religious sciences with evidence from the Qur’ān and Sunnah or prophetic traditions; (2) aspiration to unite the people involved in Da’wah; (3) familiarity with the ethics of disagreement and its discourse; (4) focus on established facts rather than allegories; (5) engagement with the people according to their level of understanding; (6) the ability to blend in with different sciences and cultural traditions of the people; and, (7) the ability to understand and acquire the skills of making comparisons and setting priorities.